PENGARUH FED RATE, INDEKS DOW JONES, NIKKEI 225, HANG SENG TERHADAP INDEKS HARGA SAHAM GABUNGAN - Wicaksono, Immanuel Satrio; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
Investment is the early capital from investors who are expected to deliver results in the future. This research aims to investigate the influence of Central Bank Interest Rate for the US, Dow Jones, Nikkei 225 and the Hang Seng To Composite Stock Price Index. The population in this research are The Fed Rate and the entire value of price index recorded the period 2010-2015. Sample selection technique used is saturated sampling method. The number of samples is 72 samples for each of the variables. Data analysis techniques used in this research is multiple linear regression analysis. The analysis of this study indicate The Fed Rate does not effect to Composite Stock Price Index . The Dow Jones has positive effect to Composite Stock Price Index, the Nikkei 225 is not a positive effect to Composite Stock Price Index and the Hang Seng has positive effect to Composite Stock Price Index.
Keywords: Composite Stock Price Index (IHSG), The Fed Rate, Dow Jones Index, Nikkei 225 Index and Hang Seng Index